Diagnostic accuracy of ultrasound for dysphagia in neurological disorders including stroke: a systematic review and meta-analysis - Yang, Liu; Liu, Dongxue; Shuang, Dai; Shuang, Liang; Wang, Yujiao; Gao, Lan (Frontiers in Neurology, 2025)
ObjectiveTo investigate the diagnostic accuracy of ultrasonography in detecting dysphagia and to compare it with other diagnostic methods.MethodsThis is a systematic review and meta-analysis of observational studies. The literature was searched in multiple databases, including the Cochrane Central Controlled Trials Registry (a global database of controlled trials); MEDLINE, EMBASE, and Web of Science (biomedical, pharmacological, and multidisciplinary citation databases, respectively); CINAHL (focusing on nursing and allied health research); and Chinese databases including Wanfang Data, CNKI, and VIP (covering academic, scholarly, and scientific-technical literature). Only articles published in the English and Chinese languages were included. Studies were eligible if they compared the accuracy of ultrasound testing with that of other diagnostic methods in dysphagia patients. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) criteria (a tool for evaluating bias risk in diagnostic accuracy studies) were used to assess the risk of bias following standard procedures.ResultsWe included eight studies involving a total of 538 patients with dysphagia: seven trials for post-stroke dysphagia and one trial for dysphagia in children with cerebral palsy. The combined results showed that the sensitivity and specificity of ultrasound were 0.81 (95% CI 0.73–0.87) and 0.86 (95% CI 0.76–0.93), suggesting that the diagnostic performance of ultrasound is reliable for detecting dysphagia in patients.